2009
DOI: 10.1002/ar.20968
|View full text |Cite
|
Sign up to set email alerts
|

From Genes to Proteins in Mendelian Parkinson's Disease: An Overview

Abstract: Parkinson's disease (PD) is the second most common neurodegenerative disorder after Alzheimer's disease. A progressive movement disorder typified by the production of bradykinesia, tremor, rigidity, and impairment of postural reflexes, PD is characterized by a depletion of dopamine in the striatum. For the last decade, several Mendelian forms of PD have been identified. Mutations in these genes potentially lead to autosomal dominant (a-synuclein and LRRK2), or autosomal recessive PD (Parkin, PINK1, DJ1, and AT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 109 publications
(110 reference statements)
0
12
0
Order By: Relevance
“…Recent reports have proposed many contributing pathogenic factors leading to the selective loss of nigral dopaminergic neurons including mitochondrial dysfunction, oxidative stress, apoptosis, excitatory neurotoxicity, toxic exposure, environmental factors, calcium overload, iron metabolic abnormalities, aging of the nervous system, inheritable factors and immune abnormalities [14,15]. However, oxidative stress is a common process present in various diseases.…”
Section: Discussionmentioning
confidence: 98%
“…Recent reports have proposed many contributing pathogenic factors leading to the selective loss of nigral dopaminergic neurons including mitochondrial dysfunction, oxidative stress, apoptosis, excitatory neurotoxicity, toxic exposure, environmental factors, calcium overload, iron metabolic abnormalities, aging of the nervous system, inheritable factors and immune abnormalities [14,15]. However, oxidative stress is a common process present in various diseases.…”
Section: Discussionmentioning
confidence: 98%
“…Aside from the known monogenic mutations responsible for familial cases, idiopathic PD likely stems from a combination of genetic predispositions and environmental risk factors. During the past two decades, awareness that genes implicated in familial forms of the disease, including SNCA (Kay, Factor, Samii, Higgins & Griffith, ; Kruger, Vieira‐Saecker, Kuhn, Berg & Muller, ), Parkin (Abbas et al., ), PINK1 (Valente, Salvi, Ialongo, Marongiu & Elia, ) and DJ‐1 (Choi, Sullards, Olzmann, Rees & Weintraub, ) and most particularly LRRK2 (Horowitz & Greenamyre, , ; Martin, Kim, Dawson & Dawson, ; Pirkevi et al., ), may also play a role in idiopathic PD has represented a major milestones in the advance and direction of PD research. It suggested that studying specific molecular or cellular deficits induced by single gene mutations could help unveiling disease mechanisms and open the way to the discovery of novel therapeutic targets and treatments.…”
Section: Parkinson's Diseasementioning
confidence: 99%
“…Like α-syn, leucine rich repeat kinase 2 (LRRK2) gene inheritance in PD presents an autosomal dominant pattern (Hamilton, 2004). LRRK2 is a large cytoplasmic 2527-aa protein thought to play a role in the formation of pathological aggregates, the increase of oxidative stress and reactive oxygen species (ROS), resulting in neuronal autophagy and apoptosis (Horowitz & Greenamyre, 2010a;Pirkevi, Lesage, Brice & Basak, 2009). Also known as Dardarin, the LRRK2 protein is encoded by gene located on chromosome 12 in the PARK8 region.…”
mentioning
confidence: 99%
“…4 Recently, independent genomewide association studies (GWAS) established an unequivocal role for common genetic variants in the etiology of PD [5][6][7][8][9][10][11] and suggested a population-specific genetic heterogeneity, with SNCA, PARK16, BST1 and LRRK2 as shared risk loci for PD, [6][7][8]10,11 and MAPT as an European-specific risk locus. 6,7 Besides, variation in the GAK/DGKQ, 5 the HLA region 10 and a locus in chromosome 12q24 11 has been proposed to exert a risk for PD in different European populations.…”
Section: Introductionmentioning
confidence: 99%